The relationship between anxiety and sexual activity in climacteric women in facing menopause in Soropadan Posyandu and Sleman district - Ayu, Suci Musvita; Sofiana, Liena; Triwulandari, Ika (International Journal Of Community Medicine And Public Health, 2020)
Background: Pre-menopause is the beginning of a climacteric transition, which starts several (2-5) years before the menopause comes. Symptoms that arise are changes in the menstrual cycle becoming irregular, the menstrual cycle lengthens, then menstruation will stop. Changes in reproductive organs will affect the composition of hormones in the reproductive organs. Decreasing hormones can reduce sex desire. Psychological symptoms are decreased memory, anxiety, irritability, stress and depression. Psychological factors such as anxiety can affect a person’s sexual function. This study was conducted to determine the relationship between anxiety and sexual activity in climacteric women in facing menopause at Soropadan Posyandu, Sleman Regency. Methods: This research employed quantitative methods with observational analytic research design with cross sectional approach. The research sample was 44 respondents in Soropadan Posyandu Sleman Regency. The measurement was done using a questionnaire to measure anxiety and sexual activity. The data analysis was done using univariate and bivariate analysis. Results: Chi square statistical test showed the p value of anxiety with sexual activity which was 0.653 (p<0.05). Conclusions: There is no relationship between anxiety and sexual activity in climacteric women in the face of menopause in Posyandu Soropadan, Sleman Regency.